PROCESSES AND FINANCIAL CHARACTERISTICS IN ENTERPRISES OF RAW MATERIALS FOR WALL CONSTRUCTION - Ramazonov Ghalibjon; Ubaydullayeva Mumtozbegim (PEDAGOGS, 2024)
Annotation: The newly restored and rapidly developing wall building materials industry is a very necessary and strategic role for the economy of Uzbekistan.